Taking care. Nursing towards Covid-19 patients during the pandemic emergency in Italy: a qualitative study - Moretti, Chiara; Ceccaroni, Sara Elettra; Confortini, Riccardo; Roncaglio, Clelia Malvina; Lionetto, Valentina; Ndocaj, Kristine; Festa , Lucia; Calderone, Carlotta; Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the study: The Covid-19 pandemic has clearly impacted the Italian healthcare system. The growing number of patients in critical conditions has required a reorganization of the hospitals wards and of other healthcare structures, by changing the working routines of health professionals. The aim of the study is to explore if and how the nursing care towards Covid-19 positive patients have changed during the pandemic. Method: Qualitative study with a phenomenological approach conducted through semi-structured interviews. Interviews have been carried out during the months of October and November 2020. Our research involved 21 nursing professionals attending post-graduate courses at the Department of Medicine and Surgery of the University of Parma (academic year 2019/2020) and who have worked during the pandemic period in health services structures and organizations. Results: The interviews showed how, during the period of the pandemic emergency, the care relationship between nurses and patients has changed because of the priority given to clinical and technical practices, in some cases, “life-saving”. This happened due to different factors such as the nurses’ fear of being infected by the virus and the lack of a sufficient time to ensure an holistic and integrated approach towards an increasing number of patients in highly complex conditions. Thus, the dimension of caring has been consciously overshadowed. Conclusions: The health emergency that has hit Italy since the first months of 2020 has shown structural limits and gaps of public health policies, hospital settings and national health services organization that already existed in the pre-pandemic period. It also highlighted how, even before Covid-19, nursing was already in part denoted by a loss of caring, a missed nursing care.